Dendritic cell functions: Learning from microbial evasion strategies. Issue 2 (March 2015) - Rescigno, Maria
Highlights Microorganisms can interfere with recognition, antigen processing and presentation, and killing by macrophages and dendritic cells. Each pathogenic microorganism has developed unique strategies to evade APC recognition. Understanding how microorganisms evade the immune response can shed light on how APCs interact with microorganisms.